A New Stage of the Caregiving Career: Informal Caregiving After Long-term Institutionalization. (10th November 2020) - Robison, Julie T; Shugrue, Noreen A; Fortinsky, Richard H; Fabius, Chanee D; Baker, Kristin; Porter, Martha; Grady, James J
Abstract: Background and Objectives: The "unexpected career" of caregiving has previously been conceptualized in stages: community care through institutional placement/residence, ending with death of the care recipient. Transition programs such as Money Follows the Person (MFP) created a new stage of the caregiving career, caring for someone post–long-term institutionalization, about which little is known. Using Pearlin's Caregiver Stress Process Model, this study explores effects on caregivers from the return of their loved ones to the community after a long-term institutional stay. Research Design and Methods: Cross-sectional surveys of 656 caregivers of persons transitioned through Connecticut's MFP program 2014–2018, completed 6 months posttransition. Results: Regardless of the age/disability of the care recipient, and despite experiencing high caregiving intensity, caregivers experienced less burden, anxiety, and depression, and higher benefits of caregiving than demonstrated in literature for the general caregiving population. Most felt less stressed than before and during the participant's institutional stay. Factors associated with worse outcomes included worry about safety, strained finances, missing work, and desiring additional services. Black and Hispanic caregivers experienced lower burden and anxiety and higher benefits of caregiving than White caregivers. Discussion and Implications: By providing community supports to participants, transition programs can have broad ancillary benefits for caregivers and improve outcomes in the Pearlin model, lessening potentially deleterious effects of an unexpected return to intensive caregiving duties after institutional placement. Positive results for Black and Hispanic caregivers may reflect cultural expectations in caring for family that buffer the adverse effects of caregiving.